Cooking with kids helping children learn in the kitchen - Subida, Rory C. (Anvil, 2008)
"Children develop cooking skills at different rates and so the recipes in the cookbook are categorized based on degree of ease and difficulty to match activity levels of the different age groups from 3 years old to 14 years old. Topics like kitchen hygiene and nutrition facts are likewise included to create safety awareness and the importance of health and nutrition. The recipes in this cookbook allow kids to develop various skills such as: Reading Skills ? while identifying the different ingredients and tools needed in the recipe; Math Skill ? while measuring the different ingredients to be used for the recipes; Motor Skills ? from the recipes procedures like stirring and mixing, beating and whisking ingredients; proper use of knife and can opener with supervisions, setting the table; Creativity Skills ? from the different activities in the preparation of chocolate etching, molding and shaping of cookies, decorating and icing cupcakes. The cookbook recommends parental guidance in doing all the cooking activities."--www.themayakitchen.com